2017
DOI: 10.1021/acs.est.7b03585
|View full text |Cite
|
Sign up to set email alerts
|

Emission Changes Dwarf the Influence of Feeding Habits on Temporal Trends of Per- and Polyfluoroalkyl Substances in Two Arctic Top Predators

Abstract: We monitored concentrations of per- and polyfluoroalkyl substances (PFASs) in relation to climate-associated changes in feeding habits and food availability in polar bears (Ursus maritimus) and arctic foxes (Vulpes lagopus) (192 plasma and 113 liver samples, respectively) sampled from Svalbard, Norway, during 1997-2014. PFASs concentrations became greater with increasing dietary trophic level, as bears and foxes consumed more marine as opposed to terrestrial food, and as the availability of sea ice habitat inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 99 publications
5
48
0
Order By: Relevance
“…For example, median concentrations of ∑CHLs were about 3.5 times higher in bears with a predominantly marine diet at the highest trophic level compared to the bears with a mixed diet at the lowest trophic level. Our results are in agreement with previous findings, which indicated that bears with a predominantly marine diet and higher trophic level accumulated higher concentrations of pollutants than bears at a lower trophic level, which fed on a mixed diet including terrestrial prey 20,24,44,70 .…”
Section: C) the Role Of Feeding Habitssupporting
confidence: 93%
See 1 more Smart Citation
“…For example, median concentrations of ∑CHLs were about 3.5 times higher in bears with a predominantly marine diet at the highest trophic level compared to the bears with a mixed diet at the lowest trophic level. Our results are in agreement with previous findings, which indicated that bears with a predominantly marine diet and higher trophic level accumulated higher concentrations of pollutants than bears at a lower trophic level, which fed on a mixed diet including terrestrial prey 20,24,44,70 .…”
Section: C) the Role Of Feeding Habitssupporting
confidence: 93%
“…Pollutants were ln-transformed to meet model assumptions. "Sampling year" was included in each model as a random factor to account for temporal variation of pollutant levels in Barents Sea polar bears70,71 . As suggested by Zuur et al72 , we used the restricted maximum likelihood estimation (REML) method to avoid any potential biased estimations.…”
mentioning
confidence: 99%
“…Furthermore, in vitro studies on Baikal seal and mouse indicate that PFASs act additively on PPARA at concentrations relevant for polar bears 15,71 . PFNA-mediated changes in PPARA functions are likely to increase in the future, as PFNA concentrations have increased 2.5% per year in Barents Sea polar bears during the period 2000–2014, whereas PFOS concentrations have been stable since 2009 72 . Furthermore, with the declining sea ice the Barents Sea, there is an increase in the use of offshore areas at the eastern Barents Sea by polar bears 73 , and bears using these areas have higher PFAS concentrations than those which stay close to the Svalbard Archipelago 74 .…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, PFTrDA was not measured in the current study. However, PFTrDA has been detected in numerous high trophic level arctic species at concentrations comparable to PFOA (Rotander et al, 2012; Routti et al, 2017). Future studies should assess exposure to long chain PFASs in the Arctic.…”
Section: Discussionmentioning
confidence: 99%